Analysis of the agro-industrial reality in the Arauca-Arauca municipality (Revista "Boletín el Conuco", 2020)
The Municipality of Arauca has had a decelerated development process in the agricultural and agroindustrial sector, which has been framed within the armed conflicts that take place in the country, the present state weakness, the disarticulation and deficiency that exists in the road mesh , Institutional development, corporate and trade weakness, and high corruption rates in the public sector. The present article intends to show the valuation of the technological infrastructure, the organizations and the institutional support. To achieve this objective, the AHP or Hierarchical Analytic Process was used, using secondary information sources such as: policy documents, documents of public and private entities, studies and statistics of United Nations agencies and academic documents. The analysis of the information collected has led to the determination that the production chain of cocoa and meat-dairy products have the potential of agro-industrial development, but there are no objective conditions to consolidate the banana and forestry.
Keywords: productive bets; rural development; rural energization; economic planning; agroindustrial valuation